Exogenous α-lipoic acid mitigates lead (Pb) toxicity in tomato seedlings by regulating metabolites, nutrient uptake, antioxidant defense and redox balance maintenance - Ramadan, Khaled M. A.; Hashedi, Sallah A. Al; AlShoaibi, Adil; Sattar, Muhammad Naeem; Darwish, Doaa Bahaa Eldin; Albalawi, Khulud S.; Alzuaibr, Fahad Mohammed; Bendary, Eslam S.A.; Khalil, Hala B.; Ghazzawy, Hesham S.; Ali, Mahmoud Adel Ahmed; Ibrahim, Mohamed F. M. (Frontiers in Plant Science, 2025)
Water contamination with heavy metals drastically affects plant growth and development. It is more dangerous than other contamination sources due to its cumulative impact over time through plant irrigation. Lead (Pb) is one of the most prevalent and hazardous heavy metals that significantly impede plant growth and development in terrestrial ecosystems. α- lipoic acid (ALA) is a naturally occurring dithiol antioxidant, strong ROS scavenger and metal chelator. Herein, this study was conducted to explore the role of exogenous ALA (0.1 mM) in reducing the Pb-phytotoxicity in tomato seedlings irrigated with Pb contaminated water (250 ppm for 45 days after transplanting). Exposing plants to Pb stress significantly inhibited plant growth, photosynthetic pigments, mineral homeostasis and cell membrane integrity compared to the control plants. In contrast, ALA application markedly revealed a significant improvement in these traits by reinforcing the antioxidant defense systems including superoxide dismutase, guaiacol peroxidase, catalase, glutathione reductase and the major reduced components of ascorbate glutathione cycle. Moreover, ALA significantly enhanced N, P, K, Ca and Fe, reduced Pb uptake and restricted the Pb-induced oxidative damage by reducing the hydrogen peroxide, malondialdehyde and inhibiting the activity of Lipoxygenase. The regression analysis exhibited that ALA demonstrated various significant relationships between the uptake of Pb and the major components of ascorbate glutathione cycle in both leaf and root. In conclusion, our findings deciphered the potential functions of ALA in alleviating Pb-phytotoxicity and enhancing the redox balance of tomato seedlings by enhancing the ratio between the reduced glutathione/oxidized glutathione and reduced ascorbate/dehydroascorbate.